Influence of Influencer Marketing, E-Wom on Timephoria Purchase Decisions Via Tiktok, Mediated by Fomo - Dhiannisa Shabrina Yuwono; Ratih Hasanah Sudradjat (Eduvest - Journal of Universal Studies, 2025)
This research aims to analyze the influence of Influencer Marketing and Electronic Word of Mouth (E-WOM) on purchasing decisions of Timephoria cosmetic products on the TikTok social media platform, with Fear of Missing Out (FOMO) as a mediating variable. The growing use of TikTok as a marketing tool and the high consumer engagement with influencer-created content serve as the main background of this research. A quantitative approach was used with Structural Equation Modeling-Partial Least Squares (SEM-PLS), involving 140 TikTok users in Indonesia. The results indicate that both influencer marketing and E-WOM significantly influence FOMO and purchase decisions. Moreover, FOMO significantly mediates the relationship between influencer marketing, E-WOM, and purchase decisions. These findings highlight the importance of marketing communication strategies that leverage influencer credibility and the power of online reviews in shaping consumer behavior. This study contributes to the development of the Elaboration Likelihood Model (ELM) in the digital marketing context and offers practical implications for cosmetic businesses in designing effective promotional strategies on social media.